Evolution in the surface modification of textiles: a review - Nadi, Ayoub; Boukhriss, Aicha; Bentis, Aziz; Jabrane, Ezzoubeir; Gmouh, Said (Textile progress, 2018)
The development of technical textiles allows the introduction of new, interesting and original multi-functionalities in textiles through development of the architecture of fibres, yarns and fabrics, their morphology and surface functionalization without altering their physico-chemical proprieties. This issue of Textile Progress reports different techniques used to impart new functionalities to the surfaces of textiles during the last decade. Following a short, context-setting historical introduction, the preparatory processes which need to be applied to textile matrices to make them clean and ready for functionalization are examined prior to a comprehensive review of techniques and research related to the development of functional textiles ranging from the more-traditional techniques through to more-recent developments. The challenge now is to bring new performance features to bear whilst maintaining environmental sustainability, chemical toxicological acceptability, high performance and cost effectiveness. In this context, the review reports on developments in the use of polymerization, nanotechnologies, plasma treatment, electrospinning, microencapsulation and sol gel techniques to impart novel properties to a textile surface such as water-repellent, flame-retardant and antibacterial properties.